Modellbildung und Simulation von mobilen Arbeitsmaschinen - Untersuchungen zu systematischen Modellvereinfachungen in der Simulation von Antriebssystemen am Beispiel Bagger - Rose, Steffen (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2017)
In the present work a systematic approach is presented. With this approach it is possible to take concerted simplifications in building models of power train systems of mobile machines. The adopted systematic simplifications are aimed essentially of reducing the order of the system. The basis for this is the introduction of hydraulic replacement elements. Their mathematical structure is based on reduced-dynamic, stationary and event-oriented considerations.